Assessment of the level of Realization of Sustainable Development Goals: Evidence from Manufacturing Firms in Nigeria - Onuoha, Nnachi Egwu; Okoye, Gregory Onuora (Advances in Social Sciences Research Journal, 2020)
ABSTRACT Studies on the extent of realization of the sustainable development goals from the perspective of manufacturing firms in Nigeria are sparse. Accordingly, this study investigates: the extent sustainable development goals have been realized by manufacturing firms in Nigeria; the extent the social strand of sustainable development goals has been realized by the firms; the extent the environmentalstrand of sustainable development goals has been realized by the firms and the difference between the extent of realization of the social and environmental strands of the sustainable development goals by these firms. To achieve the above objectives, primary data set was collected from the 2017 annual reports of ten manufacturing firms in Nigeria using content analysis. The collected data were analyzed using t test and wilcoxon signed rank test for related samples. The results of the analysis indicate that: the extent of realization of sustainable development goals by manufacturing firms in Nigeria is insignificant, the extent of realization of the social strand of sustainable development goals by the firms is significant and the extent of realization of the environmental strand of sustainable development goals by the firms is insignificant. The result further shows a significant difference between the extent of realization of the social and environmental strands of the sustainable development goals by the firms. The results of this study offer insight that would enable policy makers to insist on tighter environmental measures for manufacturing firms in Nigeria.